2017
DOI: 10.2152/jmi.64.181
|View full text |Cite
|
Sign up to set email alerts
|

Three-year survival in primary cardiac angiosarcoma

Abstract: : A healthy 18-year-old girl was referred to our hospital for further evaluations of cardiac angiosarcoma. Transthoracic echocardiography showed an immobile 4.6 cm 3.7 cm cardiac mass. The mass was occupying right atrial chamber and partially, invading into annulus of tricuspid valve on transesophageal echocardiography. At surgery, the mass was seen to be protruding from right atrial appendage and adhering to right side of pericardium. The histological findings were consistent with cardiac angiosarcoma and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…Around 75% of angiosarcomas are located in the right atrium. The lateral/free wall is the most common site, while the interatrial septum is frequently preserved [4,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 75% of angiosarcomas are located in the right atrium. The lateral/free wall is the most common site, while the interatrial septum is frequently preserved [4,7].…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnea is present in 59%-88% of patients with such a diagnosis [2,7]. It is usually multifactorial: vulnerability of the tricuspid valve due to the location in the right atrium, pericardial effusion with or without cardiac tamponade, right ventricle obstruction due to tumor's growth, pleural effusion, and lung metastasis [4,9,11,12]. Less frequently, patients may present hemopericardium, hemoptysis, anemia, pulmonary embolism, and superior vena cava syndrome [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…For resectable cases, surgical resection combined with chemotherapy and local radiotherapy might be useful. Fukunaga et al recently reported a three-year survival in a patient with primary cardiac angiosarcoma, who received surgical resection followed by chemoradiotherapy (10).…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Surgical resection remains the first-line treatment of choice when no evidence of metastases exists and myocardial resection is reparative. [ 20 ] If the tumor is resectable, adjuvant therapies, including chemotherapy, radiotherapy and targeted therapy, can improve the chances of survival because of the high probability of metastasis. [ 21 24 ] Among the surgical therapeutic methods, heart transplantation has also been suggested, although many moral and social dilemmas exist.…”
Section: Discussionmentioning
confidence: 99%